Occupational Physical Activity and Regular Exercise Are Inversely Correlated with Thyroid Function in Patients with Hashimoto’s Thyroiditis - Marko Vuletić; Dean Kaličanin; Ana Barić Žižić; Maja Cvek; Sanda Sladić; Veselin Škrabić; Ante Punda; Vesna Boraska Perica (Diseases)
Objective: We evaluated correlations of occupational physical activity (OPA) and recreational exercise (RE), respectively, with thyroid function in patients with Hashimoto’s thyroiditis (HT). Methods: We included 438 individuals with clinically diagnosed HT. Information on OPA and RE were collected through a self-report questionnaire. We assessed correlations between clinical phenotypes (TSH, T3, T4, fT4, TgAb, TPOAb, thyroid volume, vitamin D) and physical activities (OPA and RE) in all HT patients (ALL) and in two severity-based subgroups of patients (MILD and OVERT). Results: The main novel findings are significant correlations between increase in OPA and (i) a decrease in fT4 (OVERT, r = −0.265, p = 0.0002 and ALL, r = −0.138, p = 0.006); (ii) an increase in TSH (ALL, r = 0.124, p = 0.014 and OVERT, r = 0.183, p = 0.013) and (iii) an increase in TPOAb antibodies (ALL, r = 0.101, p = 0.045). In contrast, we observed correlations between increase in RE and: (i) a decrease in TSH (OVERT, r = −0.238, p = 0.001); (ii) a decrease in TgAb antibodies (OVERT, r = −0.194, p = 0.01) and (iii) an increase in vitamin D levels (ALL, r = 0.146, p = 0.005 and OVERT, r = 0.173, p = 0.023). Conclusions: Our results suggest that, unlike RE, OPA correlates with decreased thyroid function and increased thyroid autoimmunity. Our study proposes that the PA health paradox also applies for the thyroid health.